2014
DOI: 10.1071/rd12369
|View full text |Cite
|
Sign up to set email alerts
|

The value of second polar body detection 4 hours after insemination and early rescue ICSI in preventing complete fertilisation failure in patients with borderline semen

Abstract: Abstract. In this study we evaluated the value of short-time insemination and early rescue intra-cytoplasmic sperm injection (ICSI) in preventing the occurrence of complete fertilisation failure for mild or moderate male infertility patients. A total of 866 couples with borderline semen who underwent in vitro fertilisation treatment in 2010 were included. Regular insemination was performed between January and June of 2010 and short-term insemination was performed from July through December 2010, where, as earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
0
18
1
Order By: Relevance
“…To determine the need for rescue ICSI based on the extrusion of 2PB 4-6 h after insemination has become a widely recognised approach (Chen & Kattera, 2003;Xiong et al, 2011;Zhu et al, 2011a,b). At 4-6 h after fertilisation, the extrusion rate of 2PB ranges from 78 to 86% ( Van den Bergh et al, 1995;Suppinyopong et al, 2000;Jin et al, 2014). For a few cases where more than 6 h is required for the extrusion of 2PB, rescue ICSI may misjudge the fertilised oocytes with the 2PB not extruded as unfertilised oocytes, leading to polyploidy.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To determine the need for rescue ICSI based on the extrusion of 2PB 4-6 h after insemination has become a widely recognised approach (Chen & Kattera, 2003;Xiong et al, 2011;Zhu et al, 2011a,b). At 4-6 h after fertilisation, the extrusion rate of 2PB ranges from 78 to 86% ( Van den Bergh et al, 1995;Suppinyopong et al, 2000;Jin et al, 2014). For a few cases where more than 6 h is required for the extrusion of 2PB, rescue ICSI may misjudge the fertilised oocytes with the 2PB not extruded as unfertilised oocytes, leading to polyploidy.…”
Section: Discussionmentioning
confidence: 96%
“…Observing the extrusion of the 2PB after granular cell removal is a key indicator of fertilisation. Jin et al (2014) observed the 2PB of 5696 IVF oocytes 4 h after their fertilisation and found that extrusion of the 2PB occurs 4 h after fertilisation for 86.3% of the oocytes, of which 93.3% of the oocytes are found to be fertilised on the day after OPU. The oocytes extruded from the 2PB observed in group 2 in our study had a fertilisation rate of only 59.13%, which is lower than that observed in group 3 (93.3%).…”
Section: Discussionmentioning
confidence: 96%
“…Xiong's report indicated that cumulus cells removal at 6 h of insemination was a relatively safe operation with comparable normal fertilization rate and clinical pregnancy rate [26]. Short term co-culture for 4 h after insemination was also used for preventing complete fertilization failure in patients with bordline semen [27]. In our center, early rescue ICSI was performed after 5 h post-insemination for none of the MII oocytes had second polar body extrusion, which meant complete fertilization failure.…”
Section: Introductionmentioning
confidence: 94%
“…The patient underwent two failed IVF/ICSI attempts ( Table 2). In the first IVF cycle, she underwent short-time insemination and early-rescue ICSI at AnHui Women and Child Health Care Hospital as previously described [17,18]. Twenty-three MII oocytes were retrieved, but none were normally fertilized after early-rescue ICSI.…”
Section: Outcomes Of Icsi-aoamentioning
confidence: 99%